2014
DOI: 10.1617/s11527-014-0359-7
|View full text |Cite
|
Sign up to set email alerts
|

Current practice and open issues in strengthening historical buildings with composites

Abstract: Modern techniques and innovative materials are often quite rapidly proposed and allowed in current practice, even for restoration of historical constructions, in which essential preservation criteria must be taken into account. The considerable variability and complexity of masonry structures and types means that choosing the most appropriate structural models and interventions is particularly difficult, since they must be based on suitable knowledge of both existing and new materials, and on their interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
103
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 149 publications
(103 citation statements)
references
References 21 publications
0
103
0
Order By: Relevance
“…The use of inorganic matrices, in place of the epoxy resins adopted in the already wellestablished Fibre Reinforced Polymers (FRPs), provides important advantages in terms of fire resistance, vapour permeability, time and cost of installation, especially on irregular surfaces [1]. Additionally, the use of suitable mortars may provide reversibility and physical/chemical compatibility with the substrate, allowing for the fulfilment of the preservation criteria required in applications to cultural heritage [2].…”
Section: Introductionmentioning
confidence: 99%
“…The use of inorganic matrices, in place of the epoxy resins adopted in the already wellestablished Fibre Reinforced Polymers (FRPs), provides important advantages in terms of fire resistance, vapour permeability, time and cost of installation, especially on irregular surfaces [1]. Additionally, the use of suitable mortars may provide reversibility and physical/chemical compatibility with the substrate, allowing for the fulfilment of the preservation criteria required in applications to cultural heritage [2].…”
Section: Introductionmentioning
confidence: 99%
“…Innovative strengthening systems based on textiles embedded into inorganic matrices have been recently proposed [1,2], which, compared to FRPs, ensure better performances at high temperatures, better material compatibility and vapour permeability, lower cost and time of installation on uneven surfaces, and are therefore suitable especially for use on masonry substrates. Furthermore, mortarbased reinforcements appear particularly promising for application to cultural heritage, for which additional specific requirements must be satisfied: (i) respect of authenticity in terms of materials and structural behaviour, (ii) principle of minimum intervention, (iii) reversibility, intended as substitutability and removability, (iv) compatibility with original substrates and decorative settings, (v) durability [3].…”
Section: Introductionmentioning
confidence: 99%
“…A limited number of laboratory studies have been carried out to date, devoted to material behaviour and composite-to-substrate bond performance [6][7][8][9][10][11] as well as to rehabilitation solutions for both masonry [12,13] and reinforced concrete [14,15] structures. Despite some real applications already exist [3,16,17], a deeper knowledge needs to be developed before mortar-based systems can be confidently used for safeguarding existing structures, especially when belonging to the built heritage.…”
Section: Introductionmentioning
confidence: 99%
“…that can shorten the lifespan of the structure and alter its esthetic appearance. Various research works have demonstrated that EB materials find appropriate solutions and perform well when applied to masonry structures that are at severe risk of deterioration and collapse over time [1][2][3].…”
Section: Introductionmentioning
confidence: 99%